Resting cardiovascular function and athletic performance in female soccer players - Perrotta, A. S.; Correa, C. J.; Khan, A. D.; Day, B. D.; Warburton, D. E. R.; Ramos, J. (Science & Sports, 2024)
Introduction This study examined resting cardiovascular function, when examined immediately before physical testing and its association to maximal cardiorespiratory and musculoskeletal performance in female soccer players. Summary of facts and results 21 female soccer players training as part of a collegiate team were participants over a six-month period that included six data collections separated by 30-day intervals. Indices of cardiovascular function included; cardiac output, stroke volume, systemic vascular resistance, heart rate variability (HRV) and blood pressure. Maximal cardiorespiratory and musculoskeletal performance measures included; vertical jump, lower body power, 5 and 10 m running speed, and the YoYo intermittent recovery test level-1. Simple (r) and multivariable analysis (R2) was utilized to examine the association between cardiovascular function and physical performance measures. Body mass index and body fat (%) were included as covariates. Significant associations using each analysis were observed between; HRV and YoYo performance (r = 0.26; R2 = 0.21, P < 0.05), 10 m speed and mean arterial pressure (r = -0.44; R2 = 0.30, P < 0.001), 5 m speed and systolic blood pressure (r = -0.32; R2 = 0.18, P < 0.01), as well as lower body power and stroke volume (r = 0.50; R2 = 0.42, P < 0.001).